Low use of artemisinin-based combination therapy for febrile children under five and barriers to correct fever management in Benin: a decade after WHO recommendation - B. G. Damien; B. Aguemon; D. Abdoulaye Alfa; D. Bocossa; A. Ogouyemi-Hounto; F. Remoue; J.-Y. Le Hesran (BMC, 2018)
Abstract Background Artemisinin-based combination therapy (ACT), used to treat uncomplicated malaria cases, is one of the main strategies of malaria control and elimination. One of the main objectives of the Benin National Malaria Control Program's (NMCP) strategic plan is to ensure that at least 80% of uncomplicated malaria is treated with ACT within 24 h. Therefore, it was of great interest to measure whether the country case management of fever amongst children under five, adhered to the NMCP's strategic plan and look into the barriers to the use of ACT. Methods A cross-sectional survey based on a cluster and multi-stage sampling was conducted in two rural health districts in Benin. We recruited 768 and 594 children under five years were included in the northern and in the southern respectively. Data was collected on the general use of ACT and on the correct use of ACT that adheres to the NMCP's strategy, as well as the barriers that prevent the proper management of fever amongst children. To assess the certain predictors of ACT usage, logistic regression was used, while taking into account the cluster random effect. Results Among febrile children aged 6 to 59 months, 20.7% in the south and 33.9% in north received ACT. The correct use of ACT, was very low, 5.8% and in southern and 8.6% northern areas. Caregivers who received information on ACT were 3.13 time more likely in the south and 2.98 time more likely in the north to give ACT to their feverish child, PPR = 3.13[1.72-4.15] and PPR = 2.98 [2.72-3.11] respectively. Chloroquine and quinine, other malaria treatments not recommended by NMCP, were still being used in both areas: 12.3 and 3.3% in the south and 11.4 and 3.0% in the north. Conclusion In Benin, the use and the correct use of ACT for febrile children remains low. The study also showed that having received information about the use of ACT is positively associated with the use of ACT. This point highlights the fact that efforts may not have been sufficiently integrated with social communication, which should be based on the behavioural determinants of populations.